What Goes Around Comes Around: The Effects of Sanctions on Swedish Firms in the Wake of the Ukraine Crisis - Joakim Gullstrand (Lund University, School of Economics and Management, Department of Economics, 2018)
This paper focuses on the effects of sanctions on Swedish firms' sales across markets, as well as sanctions' effects on their domestic production. As a case study, the paper uses sanctions imposed on Russia and by Russia in 2014. The results suggest that the total costs of these sanctions due to a drop in sales for Swedish firms amounts to around 1 billion SEK in 2013 prices, which implies a rather limited impact on the Swedish economy overall, which amounted to a total of around 4000 billion SEK in 2013. The total impact may be divided into a target effect and a sender effect. The target effect is reflected in a 65% drop in sales of banned products in the Russian market, while the sender effect on exports outside Russia was less important. The ripple effects on other markets of these sanctions were, however, asymmetrical and complex. Sales on the domestic market was on average intact while exports to markets facing the same type of sanctions fell. The most vulnerable firms could face a loss in sales of more than 40% of their value added, and the most important firm-level mechanism, as to how firms responded in their domestic production, was financial distress. I found, however, an additional mechanism within firms regarding their export response on markets other than Russia, since the negative impact was concentrated on their fringe products, while their core business remained intact after the sanctions were implemented.
Keywords: F13; F14; F51; R11; 330; Sanction; embargo; export; production; Sweden